(3GdLed aj GdfMhs - (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe, (B337 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh GdbGSe CbSGe GdcdGe KdGKI (B: (3GSe haYd hMQa s
(3BNQgG (B:s
(3ajMPahf Gdfhf , hcPdc jaYdhf Hcd bHjdI JXQ ajgG dGe GdJYQja hgj dZI YQHjI aGTjI Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3ChdgG ChQGb HNW eZGjQ bOjes
(3hYdi MhGTjgG JYdjbGJ hJUMjMGJ hHBNQgG ebGHdI SfI (B800 (3g` hELGRI SfI (B855 (3g`s
(3hJedjc bOjes
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs